2020
DOI: 10.1057/s41599-020-0498-0
|View full text |Cite
|
Sign up to set email alerts
|

Work and family conflict analysis of female entrepreneurs in Turkey and classification with rough set theory

Abstract: Entrepreneurs face numerous challenges and experience conflicts in their daily lives. However, it is clear that female entrepreneurs have more conflicts than male ones due to society's perception of women and various expectations from them, and consequently, these conflicts affect women's investment decisions. In this study, especially conflict levels of female entrepreneurs at work and in family have been investigated. Also, this study dwells upon how the roles that female entrepreneurs play in family and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The author identified that the topic of entrepreneurial tendencies is the leading topic among Turkish researchers publishing in national scientific journals. A similar tendency can be seen in articles available via Web of Science in the last two years, as many scholars are engaging in measuring entrepreneurial tendencies (Gürel et al, 2021;Özcan et al, 2021;Yalçıntaş et al, 2021), understanding the impact of Syrian refugee entrepreneurs on Turkish economy (Baktır & Watson, 2021;Chang, 2021;Kachkar, 2019) and how women entrepreneurs are changing the entrepreneurship scene in Turkey (Ármane et al, 2021;Bozoğlu Batı & Armutlulu, 2020;Erdoğan, 2020;Kurteğe Sefer, 2020). (Öner & Kunday, 2016) notice that entrepreneurship support started to increase and become more visible since 2006.…”
Section: Literature Reviewmentioning
confidence: 60%
See 1 more Smart Citation
“…The author identified that the topic of entrepreneurial tendencies is the leading topic among Turkish researchers publishing in national scientific journals. A similar tendency can be seen in articles available via Web of Science in the last two years, as many scholars are engaging in measuring entrepreneurial tendencies (Gürel et al, 2021;Özcan et al, 2021;Yalçıntaş et al, 2021), understanding the impact of Syrian refugee entrepreneurs on Turkish economy (Baktır & Watson, 2021;Chang, 2021;Kachkar, 2019) and how women entrepreneurs are changing the entrepreneurship scene in Turkey (Ármane et al, 2021;Bozoğlu Batı & Armutlulu, 2020;Erdoğan, 2020;Kurteğe Sefer, 2020). (Öner & Kunday, 2016) notice that entrepreneurship support started to increase and become more visible since 2006.…”
Section: Literature Reviewmentioning
confidence: 60%
“…Regarding gender, it has already been emphasized in the literature review that the number of scientific publications on the topic of women entrepreneurship is keeping on growing (Ármane et al, 2021;Bozoğlu Batı & Armutlulu, 2020;Erdoğan, 2020;Kurteğe Sefer, 2020), hence, it is worth analysing how gender and type of self-employment are associated. Regarding age group, a recent statistical analysis by the Turkish Statistical Institute (Turkish Statistical Institute, 2021b) highlights that Turkey has the youngest population in Europe, with the age group 15-24 accounting for 15,4%of the Turkish population.…”
Section: Resultsmentioning
confidence: 99%
“…The ICC2 value is 0.808, which exceeds the standard of 0.70. The average Rwg is 0.966, exceeding the minimum threshold of 0.70 (Bliese 2000).…”
Section: Methodsmentioning
confidence: 85%
“…Men's greater time commitment to the work role leaves them with less time and energy available to give to the family role. Business research has shown that women business owners experience unique difficulties and problems which limit their economic performance and jeopardise their personal feelings of achievement and satisfaction hence influencing work-family conflict [8,9].…”
Section: Effect Of Socio-demographics On Work-family Conflictmentioning
confidence: 99%